Typology Visual Guidelines for Transit-Oriented Development 3-D Incentive Zoning in East Asian Metropolitan Cities—A Case Study of Shanghai Subway-Adjacent Plots - Yuchen Zhou; Anqi Liu; Runtian Shen; Yu Yan (Buildings)
The revitalization and renewal of existing urban space is a primary objective in the redevelopment of high-density transit-oriented development (TOD) areas. In this context, offering incentive zoning bonuses is a critical tool for optimizing urban space. However, in some subway-adjacent plots with high building densities, traditional incentive zoning methods face limitations due to insufficient horizontal space. These areas increasingly rely on multi-ground public spaces to balance density with public services. This study investigates new methods of incentive zoning between commercial areas and public spaces in multi-ground public spaces within subway-adjacent plots, using 33 rail transit complexes in Shanghai, China, as the research subject. The findings are presented in the form of visual guidelines to provide guidance on architectural control, with the goal of enhancing the quality of urban public spaces. In this research, a multiple linear regression model is employed, using GNCS_AR (the ratio of ground non-commercial stay to area), which captures both efficiency and equity in public space quality, as the dependent variable. A model is developed in SPSS, incorporating independent variables such as TCA (total commercial area), POS (public open space area), PIS (public indoor space area), and MGZFs (multi-ground zoned floors). This model provides a framework for developers to manage and control public space in multi-ground settings within rail transit complexes. Research has found that MGZFs alone cannot be included as the independent variable in the model, as their absence leaves the model unable to explain three-dimensional spaces. However, incorporating the ratio of RIOPS (the ratio of indoor to outdoor public space) to MGZFs significantly improves the model’s correlation and explanatory capacity. The resulting model demonstrates that, under different POS and MGZF tiers, the influence of PIS and TCA on public space quality varies. Using a typological approach, the study categorizes these complexes into five tiers based on POS and MGZFs. Within the same tier, changes in PIS and TCA types lead to variations in public space quality. The empirical results are translated into diagrams that link data, forms, and indicators to guide the development of three-dimensional spaces. These diagrams, which can be named visual guidelines, provide practical guidelines for optimizing public spaces in these subway-adjacent plots.